Lithic technologies in sedentary societies - Horowitz, Rachel A. (Archaeologist); McCall, Grant S. (University Press of Colorado, 2019)
"Examining lithic technology in sedentary societies around the world and showcasing information that in-depth, cutting-edge, lithic analytical techniques provides. Highlighting important contributions to the field of lithics and how they can improve the study of sedentary Mesoamerican societies, as well as other ancient societies around the world"--Provided by publisher